Small Molecule Inhibitors of MDM2-p53 and MDMX-p53 Interactions as New Cancer Therapeutics - Yujun Zhao; Denzil Bernard; Shaomeng Wang (BioDiscovery, 2013)
Inactivation of the function of tumor suppressor p53 is common in human cancers. In approximately half of human cancers, the tumor suppressor function of p53 is inactivated by deletion or mutation of TP53, the gene encoding p53 protein. In the remaining 50% of human cancers, p53 tumor suppressor function can be effectively inhibited by oncoprotein MDM2 or its homolog MDMX. Since inhibition of p53 by MDM2 or MDMX protein is mediated by their direct interaction with p53, small-molecule inhibitors designed to block the MDM2-p53 or MDMX-p53 protein-protein interaction (MDM2 or MDMX inhibitors) can activate p53 in tumor cells retaining wild-type p53. In the last few years, several classes of potent, selective, and efficacious small molecule MDM2 inhibitors have been designed and developed, and six such compounds are being evaluated in clinical trials as new anticancer drugs. Additionally, non-peptide, small-molecule MDMX inhibitors have been reported. We review herein the design and development of potent small-molecule MDM2 and MDMX inhibitors.